The Effects of a Secondary School Scholarship on School Progression and Youth Outcomes: Baseline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset contains baseline survey data from 2,141 youth and their households collected as part of a randomized controlled trial (RCT) titled The Effects of a Secondary School Scholarship on School Progression and Youth Outcomes in rural Ethiopia. The study evaluates whether providing secondary school scholarships to youth from extremely poor households in remote, food-insecure kebeles improves school enrollment and progression and affects a range of non-academic outcomes.